Projektowanie i wdrażanie rachunku kosztów działań (ABC) w przedsiębiorstwie produkcyjnym ISKRA CNS Sp. z o.o. - Leszczyński, Zbigniew (Project and Implementation of Activity Based Costing in Production Firm, 2007)
The article describes projecting and methodology implementation of Activity Based Costing in a production firm. It presents information system "ABC" that has been implemented by the author of the article in a production firm.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 344-354